MID TO LATE HOLOCENE CLIMATE CHANGE IN NORTH CENTRAL MONGOLIA AS RECORDED IN THE SEDIMENTS OF LAKE TELMEN - Peck J.A.; Khosbayar P.; Fowell S.J.; Pearce R.B.; Ariunbileg S.; Hansen B.C.S.; Soninkhishig N. (My University, 2002)
A record of climatic change has been reconstructed for the past 7110 calibrated calendar (cal) years for Lake Telmen, Mongolia, based upon sedimentologic and geomorphic evidence from the lake–watershed system. Lake Telmen is a saline (presently 4 g l−1) closed-basin lake and is therefore sensitive to changes in effective moisture balance. Between 7110 and 6260 cal yr ago, conditions in the Lake Telmen region were hyperarid and a small saline (approximately 20 g l−1) lake was present. Increased effective moisture balance but still arid conditions prevailed between 6260 and 4390 cal yr ago. Since 4390 cal yr ago, generally more humid conditions prevailed in the Lake Telmen region. As the lake deepened, a hypoxic hypolimnion became established below a well-developed summer thermocline resulting in varved sediment accumulation since 4390 cal yr ago. Between about 2710 and 1260 cal yr ago, a greater than present-day effective moisture balance is recorded by a series of four lake highstand terraces. Sedimentologic profiles from lacustrine cores suggest an increase in effective moisture during the past approximately 680 cal yr.
Keywords: Holocene; Cenozoic::Quaternary::Holocene; Кайнозой::Четвертичная::Голоцен